Characteristics of Renal Function in Patients Diagnosed With COVID-19: An Observational Study - Hong, Xu-wei; Chi, Ze-pai; Liu, Guo-yuan; Huang, Hong; Guo, Shun-qi; Fan, Jing-ru; Lin, Xian-wei; Qu, Liao-zhun; Chen, Rui-lie; Wu, Ling-jie; Wang, Liang-yu; Zhang, Qi-chuan; et al. (Frontiers in Medicine, 2020)
Objective The aim of the study was to analyze the characteristics of renal function in patients diagnosed with COVID-19. Methods In this retrospective, single-center study, we included all confirmed cases of COVID-19 in a tertiary hospital in Guangdong, China from January 20, 2020 to March 20, 2020. Blood and urine laboratory findings related to renal functionwere summarized, and the estimated glomerular filtration rate (eGFR) and endogenous creatinine clearance (Ccr) were also calculated to assess the renal function. Results A total of 12 admitted hospital patients were diagnosed with COVID-19, included 3 severe cases and 9 common cases. Serum creatinine (Scr) was not abnormally elevated in all of the patients, and blood urea nitrogen (BUN) was abnormally elevated in only 25.0% of the patients. However, compared with the recovery period, the patient’s Scr and BUN increased significantly in peak of disease (p-scr =0.002 & p-bun < 0.001). By observing the fluctuations in Scr and BUN from admission to recovery, it was found that the peak of Scr and BUN appeared within the first 14 day of the course of the disease. Urinary microprotein detection indicated that the abnormally elevated rates of urine microalbumin(UMA),α1-microglobulin(A1M), urine immunoglobulin-G(IGU), and urine transferring(TRU) standardized by urinary creatinine in peak of disease were 41.7%, 41.7%, 50.0% and 16.7%, respectively. The abnormal rates of the calculated eGFR and Ccr were 66.7% and 41.7%. ConclusionScrand BUN were generally increased during the course of COVID-19. Detection of urinary microproteins and application of multiple indicators assessment could be helpful for discovering abnormal renal function in patients with COVID-19.However, the evidence is limited due to the small sample size and observational nature. Additional studies, especially large prospective cohort studies, are required to confirm these findings.